From complexity to clarity: A dematel analysis of critical blockchain technology adoption factors - Jankin, Abdul Rahman; Bujna, Marián; Lee, Chia Kuang (Penerbit Universiti Malaysia Pahang, 2024)
This exploration is initiated with resolute authentic intention of unravelling complex and intricate topics surrounding the adoption of blockchain technology in supply chain management. Thus, through the operation of DEMATEL (Decision Making Trial and Evaluation Laboratory) analysis, a methodological approach known for capturing and evaluating complex relationships is rather crucial as it could transition the complexity inherent in these factors to a state of clarity. It delves into three influences of technological factors namely, scalability, interoperability, and security that serve as decisive influence on blockchain adoption. The study explores the influence of those technological factors and the dynamic of collective impact on decision-making process in blockchain adoption within the supply chain context. The findings produced from this study hold strong implications for practitioners, policymakers, and researchers seeking to enhance the strategic adoption of blockchain technology in supply chain ecosystems.